Tanggung Jawab Bersama dalam Meningkatkan Reproduktibilitas dan Kredibilitas Psikologi Indonesia - Surijah, Edwin Adrianta (ANIMA Indonesian Psychological Journal, 2026)
Psychological studies have been found to be not highly reproducible, implying that claims based on empirical evidence may not always be fully trustworthy. The idea of improving transparency through data sharing and preregistration is important, but such solutions should be tailored to the Indonesian context. A gentle transition for journal managers and researchers is needed, rather than imposing policies that place additional burdens on any of the parties involved. Furthermore, the system should support reproducible research by preparing researchers to understand the processes and ethical aspects of data sharing, as well as by incentivizing reproducible studies.